La historia contemporánea de México y la historia global: reflexiones acerca de los “sesenta globales” - Scheuzger, Stephan (El Colegio de México, A.C., 2018)
This article proposes a reflection on the meaning of global history, both to understand a period that is considered to have been decisive for contemporary Mexican history as well as for interpreting historical phenomena in many other parts of the world. This analysis is based around the thesis that Latin American history, particularly its contemporary history, has been at the margins of global history. An analysis of the 1960s represents an important first step towards a greater integration of Latin American history in general and Mexican history in particular into the flow of global history. The object of this article is to better understand what happened in Mexico and in other countries in the region and around the world, as well as the larger processes that transcended national historical frameworks.